Evaluation of di‐magnesium malate, used as a novel food ingredient and as a source of magnesium in foods for the general population, food supplements, total diet replacement for weight control and food for special medical purposes. (6th June 2018) - ,; Younes, Maged; Aggett, Peter; Aguilar, Fernando; Crebelli, Riccardo; Dusemund, Birgit; Filipič, Metka; Frutos, Maria Jose; Galtier, Pierre; Gundert‐Remy, Ursula; Kuhnle, Gunter Georg; Lambré, Claude; et al.
Abstract: The present scientific opinion deals with the evaluation of the safety of di‐magnesium malate (DMM) proposed as a novel food ingredient and as a source of magnesium for use in foods for the general population, food supplements, total diet replacement for weight control and food for special medical purposes (FSMP), and with the bioavailability of magnesium from this source. Additional information was sought from the applicant during the assessment process. However, despite several requests, the applicant did not provide the additional data. Consequently, the Panel performed this assessment on the basis of the available data and concluded that there was insufficient scientific evidence of a difference between the proposed novel food ingredient named as DMM and magnesium malate already authorised as a source of magnesium included in Annex II to Directive 2002/46/EC. Accordingly, the Panel was unable to assess the safety of DMM as a novel food ingredient. The Panel concluded that based on the data provided it was not possible to assess the dissociation of DMM into magnesium and malic acid. The Panel further concluded that if DMM dissociates, magnesium would be available following ingestion of DMM and the availability would appear similar to values reported for other sources of magnesium already permitted. Finally, the Panel noted that the proposed use levels could result in exposures to magnesium greater than its upper level (UL) (250 mg/day) for food supplements and for food for special medical purposes.